Wake up: the regulation of dormancy release and bud break in perennial plants - Zhao, Yue; Ma, Yahui; Qiu, Hanruo; Zhou, Lijuan; He, Kunrong; Ye, Yajin (Frontiers in Plant Science, 2025)
In order to survive harsh winter conditions, perennial trees in the temperate and frigid regions enter a dormant state and cease growth in late summer after vigorous growth in spring and summer. After experiencing prolonged cold temperature and short days in winter, trees release their dormancy, and they resume growth to produce new buds in the following spring, a process known as bud break. The establishment/release of bud dormancy and bud break are crucial for the adaptations of woody plants and their survival in the natural environment. Photoperiod and temperature are key regulators in the bud dormancy and break cycle. In recent years, significant progress has been made in understanding the molecular mechanism for how photoperiod and temperature regulate seasonal growth and dormancy. Here, we summarized the regulatory network and mechanisms underlying the seasonal growth of perennial woody plants in the temperate and frigid regions, focusing on several molecular modules including the photoperiod, circadian clock, EARLY BUD BREAK 1 (EBB1) - SHORT VEGETATIVE PHASE Like (SVL) - EARLY BUD BREAK 3 (EBB3) module and hormone regulation. Through these modules, we will summarize how perennial trees release dormancy and bud break in order to better understand their differences and connections. By elucidating the interactions among these factors, we also point out the questions and challenges need to be addressed in understanding the bud dormancy and break cycle of perennial plants.